Identification of a Ferroptosis Gene Set That Mediates the Prognosis of Squamous Cell Carcinoma of the Head and Neck - Li, Chunyan; Wang, Xuemin; Qin, Rujia; Zhong, Zhaoming; Sun, Chuanzheng (Frontiers in Genetics, 2021)
Squamous cell carcinoma of the head and neck(HNSCC) is one of the six most common malignancies,HNSCC with high incidence and poor prognosis ,so far, its prognostic factors are still unclear. Iron-dependent form of cell death -ferroptosis is a new programmed cell death discovered recently, and increasing evidence indicates that ferroptosis may be a potential anti-tumor treatment. However, the prognostic value of ferroptosis-related genes (FRGs) in HNSCC is unclear. The aim of this study is to identify molecular markers associated with ferroptosis that influence the prognosis of patients with HNSCC. We used The Cancer Genome Atlas (TCGA) HNSCC tumour and normal data to identify prognostic related FRGs. A prognostic risk score based on the FRGs was constructed, and its prognostic value for HNSCC patients was studied using receiver operating characteristic (ROC) curve and nomogram analysis and validated in the Gene Expression Omnibus (GEO) database. There are 11 FRGs were significantly associated with overall survival (OS) based on univariate cox regression analysis in patients with HNSCC. We constructed a ferroptosis risk score model based on 5 genes and divided all patients into different risk group according to the optimal cut-off value (the median). Analysis of the Kaplan-Meier curves showed that patients with higher ferroptosis risk score had shorter OS (TCGA cohort: P< 0.001, GEO cohort: P< 0.001), and Gene Expression Profiling Interactive Analysis (GEPIA) further verified the relationships of the 5 genes with the prognosis of HNSCC patients. Multivariate Cox regression analysis showed that the risk score remained an independent predictor of OS after the exclusion of clinical confounders (HR> 1, P< 0.01). There were significant differences in gene function enrichment analysis and immune cell infiltration status between the two groups. In summary, the prognostic model based on 5 FRGs can be used to predict HNSCC patient prognosis. Moreover, the 5 FRGs may be treatment targets affecting ferroptosis in HNSCC, providing new ideas for the treatment of HNSCC.